Expertise, gender, and equilibrium play - Romain Gauriot; Lionel Page; John Wooders (Quantitative Economics, 2023)
Mixed-strategy Nash equilibrium is the cornerstone of our understanding of strategic situations that require decision makers to be unpredictable. Using data from nearly half a million serves over 3000 tennis matches, and data on player rankings from the ATP and WTA, we examine whether the behavior of professional tennis players is consistent with equilibrium. We find that win rates conform remarkably closely to the theory for men, but conform somewhat less neatly for women. We show that the behavior in the field of more highly ranked (i.e., better) players conforms more closely to theory. We show that the statistical tests used in the prior related literature are not valid for large samples like ours; we develop a novel statistical test that is valid and show, via Monte Carlo simulations, that it is more powerful against the alternative that receivers follows a nonequilibrium mixture.
Keywords: C12; C15; C72; 330; Minimax; mixed strategy Nash equilibrium play; natural experiment